Pyrgos Mavroraki Smelting and Melting Experiments in a Metallurgical Workshop of the Second Millennium BC - Maria Rosaria Belgiorno; Livio Pontieri (EXARC Journal)
Interpreting the cultural influences of Cyprus in antiquity has posed an issue, depending on one’s point of view or the different conclusions reached. Until the 1970s, in large part due to the extensive excavations along the northern coast of Cyprus, it seemed reasonable to recognise a plethora of Aegean traits in the island culture. Every element of the Cypriot Bronze Age was analysed and interpreted in a manner that led to comparisons with Aegean civilisations (Buchholz and Karageorghis, 1973; Acts of the International Archaeological Symposium, 1979). However, after the political upheavals in 1974, most archaeologists moved their attention to the southern part of Cyprus, and a different historical landscape came into view (Karageorghis. 1986). Links found between Cyprus and other Levantine countries, with a strong influence from the seafront civilisations, (including Egypt) were recognizable (Michaelides, Kassianidou and Merrillees, 2009). These links confirmed the island played an important role in the commercial traffic of the Eastern Mediterranean, where copper was one of the most sought-after goods (Acts of the International Archaeological Symposium, 1982). This was likely the reason for the inhabitants of the island to learn of its extensive metal resources and led them to metallurgy, albeit centuries later than other Mediterranean civilisations (Erez, 2018, chapters 5, 10, 18, 19).